Power Cable with Two Joints Experimental Analysis for Defect Assessments - Tze Mei Kuan; Azrul Mohd. Ariffin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Time domain reflectometry (TDR) is an easy technique that provides quick response which is ideal for power utility companies to conduct cable diagnostics on-site. Electricity disruption due to power cable failure is a major challenge for power utility companies due to the long length of cable installed with joints. The long time taken to diagnose the defect along the cable before electricity can be restored has not only jeopardized the reputation of power utility companies but also brings losses to the economy. Hence, this study conducts experimental analysis on cable with two joints with the application of TDR technique to reduce the electricity disruption time. This research is divided into two stages where stage 1 conducts experiments on cable with one degraded section while stage 2 looks into cable with two degraded sections. The TDR reflection characteristics are studied from stage 1 experiments and applied to stage 2 experiments to verify the consistency of the TDR reflection characteristics. The cable conditions of stage 2 experiments are predicted using the reflection characteristics from stage 1 observations and are then validated by comparing these predictions with the actual cable configuration. Results obtained from these experiments have proven that the TDR reflection characteristics are consistent and accurate which can be used to sectionalize the degraded cable section. Detail findings of all experiments conducted with the TDR application are discussed in part three of this paper.